Aggressive Behavior of Adolescents in terms of Authoritarian Parenting Perceptions - Ratna Yunita Setiyani; Icha Herawati; Fuad Nashori (Journal of Public Health Sciences, 2022)
The family is the most critical environment in early adolescent development. Every parent's parenting style in educating their children is unique. Cruel parenting and lack of warmth between parents and children or also known as US authoritarian parenting is one of the most dominant forms of parenting that can affect adolescent attitudes. This study aims to determine the relationship between adolescent aggressive behavior and perceptions of authoritarian parenting. This study uses a quantitative method with a correlational approach. Respondents in this study were aged between 15 to 21 years and still lived at home with their parents. The number of respondents in this study were 105 respondents. The sampling technique used is probability sampling technique. Data collection is done by filling out a questionnaire. Data were analyzed with Pearson Correlation Product moment. The results showed that respondents limited aggressive behavior to a very high percentage of 58.1% (61 people). While authoritarian parenting was experienced by 44.8% (47 people), it was also experienced at a very high level of 46.7% (49 people). The results of product moment analysis obtained a value of p = 0.000 (p <0.05) with a correlation coefficient of 0.892 which indicates a high close relationship.